Mutualism in Europe: characteristics and purposes: case studies in Portugal, France and Spain - Guimarães, Gonçalo Simões Cidrais (2020)
In the most recent years, the entities in the field of Social Economy have been improving their importance in the countries, answering to some needs of population, which are not answered by the State and by the private sector, fighting against the social problems created. The objective of this thesis is to evaluate the recent years of Social Economy and, more specifically, of Mutualism in Europe: the main objective is to understand which are the theoretical principles of Social Economy and Mutualism and how they are consubstantiated in practical terms, but with an economic contextualization. Other question is about the existing works in this field: in my opinion we have some studies about Social Economy and Mutualism, but not in a significant number, and they are usually more focused on historical perspectives. This work tries to complement the historical and economic perspectives of Social Economy and Mutualism in three European countries.